2020
DOI: 10.1002/adhm.201901211
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Biomaterials with a Brick‐and‐Mortar Microstructure Combining Mechanical and Biological Performance

Abstract: The fabrication of bone regeneration biomaterials, which simultaneously possess superior mechanical performances and excellent bioactivity, remains challenging because these properties are usually mutually exclusive. Herein, inspired by the brick‐and‐mortar architecture of nacre, lamellar silicate‐based bioceramic composites are successfully prepared by constructing orderly layered bioceramics infiltrated with a biomedical resin interlayer via the bidirectional freezing technique. The lamellar composites posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Clinically, treatments of bone defects caused by tumor resection, congenital disease, or trauma are big challenges, since bone repair is influenced by multiple factors. [1][2][3] With the rapid development of tissue engineering (TE) techniques, a series of biomaterials, including bioactive polymers, [4,5] bioceramics, [6,7] titanium alloy, [8] and their composites, [9][10][11][12][13][14] have been engineered into porous scaffolds for bone defect reconstruction, because porous scaffolds can provide 3D spaces for ingrowth of blood vessels and new bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, treatments of bone defects caused by tumor resection, congenital disease, or trauma are big challenges, since bone repair is influenced by multiple factors. [1][2][3] With the rapid development of tissue engineering (TE) techniques, a series of biomaterials, including bioactive polymers, [4,5] bioceramics, [6,7] titanium alloy, [8] and their composites, [9][10][11][12][13][14] have been engineered into porous scaffolds for bone defect reconstruction, because porous scaffolds can provide 3D spaces for ingrowth of blood vessels and new bone tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The studies learning from natural pearls, pearls, bones, bamboo, teeth, have provided countless inspiration for solving the problem of bone defects [ [24] , [25] , [26] ]. Pearl, consisting of calcium carbonate platelets and organic matrix, exhibits high strength, and uniform mineralization, which were mainly attributed to the hierarchical “brick-and-mortar” layered architectures [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These scaffolds displayed excellent properties including the high loading and sustained release of drugs and proteins and the improvement of the migration and differentiation of tissue cells. 91,92 In addition to the above, Feng et al reported a bio-inspired lamellar chitosan scaffold with a long range ordered porous structure. Most interestingly, the chitosan scaffold was found to be capable of inducing macrophage differentiation to the M2 phenotype that played an important role in tissue regeneration.…”
Section: Freeze-dryingmentioning
confidence: 99%